Intangible Assets, Resource Allocation and Growth A Framework for Analysis - Andrews, Dan (OECD Publishing, 2012)
This paper explores the growing importance of intangible assets as a potential source of innovation and productivity gains, and the contribution of efficient resource allocation to this process. Realising the growth opportunities implied by intangible assets depends on the ability to reallocate labour and capital to their most productive use, which is determined by the design of framework policies. The redeployment of tangible resources takes on heightened importance given the inherent difficulties in allocating intangibles efficiently. Indeed, the characteristics of intangible assets create market imperfections, which hinder the allocation of new ideas to where they can be developed most efficiently. While a number of policy instruments are typically deployed to address these market failures, the paper also explores how the growing importance of intangible assets is affecting the suitability of these policy tools. In turn, a number of policy issues are identified, spanning the financing of start-up firms, the treatment of intangibles in corporate valuation and accounting frameworks, competition policy in the digital economy and the role of intellectual property rights frameworks in rapidly growing domains such as information technology
Keywords: Economics